Guide to Using Rhizomal Perennial Peanut in the Urban Landscape - Robert E. Rouse; Elan M. Miavitz; Fritz M. Roka (EDIS, 2004)
Perennial peanut has recently shown promise as an ornamental groundcover due to its high resistance to drought, nematodes, and pathogens and its minimal fertilizer needs. This translates into savings in water, energy, dollars, and reduced impacts to the environment. It is not only beneficial to the environment since it requires no supplemental nitrogen or phosphorus fertilization or pest control, but it also is aesthetically pleasing, can be walked on, and has edible, peanut flavored flowers. This document is HS960, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: March 2004.